Tipagem molecular do papilomavírus humano e estudo imunocitoquímico da P16INK4A em pacientes com e sem lesão escamosa intra-epitelial e invasora do colo uterino - Taise Palmeiras de Freitas (2007)
The aim of this study was to investigate the presence of Human Papillomavirus (HPV) and of the viral types HPV-16 and HPV-18 with the polymerase chain reaction methods in patients with and without squamous intraepithelial lesion or invasive cervical cancer and to correlate these results with the p16INK4A immunocytochemicaloverexpression on cervical smears. Cervical samples of 129 patients from two public health of Belo Horizonte-MG, Brazil were evaluated. The DNA-HPV detection rate was significantly higher (91,5%) in positive cytopathological samples. HPV-16 or HPV-18 detection were seen in 70,83% of the high grade squamous intraepithelial lesions (HSIL)/invasive carcinoma samples, in 40% of the low grade squamousintraepithelial lesion (LSIL) samples and in 50% of the atypical squamous cells of undetermined significance/atypical glandular cells of undetermined significance (ASCUS/AGUS) samples. Among the samples with HPV-18, 44,4% showed p16INK4A immunocytochemical overexpression. The p16INK4A overexpression was 28,6%, 25,9% e 17,6% among HPV-16, undetermined HPV and negative HPV samples, respectively. There was no significant statistic association between p16INK4A overexpression and the high oncogenic viral types search in this work. The p16INK4A immunocytochemical overexpression was detected in 47,8% of the HSIL samples, in 26,7% of the LSIL, in 25% of the ASCUS/AGUS and in 16% of the negative cytological samples. There was significant statistic association between p16INK4A immunocytochemical overexpression and the presence of HSIL (p<0,01; OR=4,813; ICOR95%=1,580-14,661).